The Edukasi Pengetahuan Obat Herbal dan Obat Modern pada Santriwati SMA Kelas XI danXII PPTQ AL Furqon Magelang - Putri, Edhita; Afifah Noer (Universitas Darunnajah, Jakarta, Indonesia, 2023)
After the Covid-19 pandemic, people are now starting to go back to nature as an effort to maintain health so that they are not vulnerable to illness. This condition resulted in various sectors being affected such as education. School children have experienced a real impact due to the Covid 19 pandemic so that the learning received is not optimal. People who have adjusted after the pandemic, especially children who have returned to face-to-face learning, need to get education related to health. The phenomenon of consuming traditional medicine in the community needs to be educated to children at school. Efforts to provide education about herbal medicine and modern medicine can be done in schools. This community service activity is designed by conducting counseling on the classification of herbal medicines and modern medicines. Counseling was carried out by lecture method to Santriwati class XI and XII PPTQ Al Furqon Magelang